The impact of the Clean Air Act Amendments of 1990 on electric utilities and coal mines: evidence from the stock market - Christopher R. Knittel; Shulamit Kahn (University of California, Department of Economics, 2002)
If new environmental regulation imposes significant costs on firms, it should be detected in their stock prices. We use event study methodology to analyze whether President George H. Bush's Clean Air Act Amendment (CAAA) proposals of June 1989, which were quite different from what had been expected, depressed stock prices in affected electricity generating and coal mining companies. We find that shares of 35 electric generating companies owning Phase I power plants did not noticeably fall in value after the Bush June 1989 announcement, nor after three other possibly relevant events during the preceding year. In fact, these shares increased in value during June and July of 1989. In contrast, stock prices of 11 of the 12 coal mining companies fell after Bush announced his proposals, while stock prices of a large majority of these coal companies fell after two of the other three events (although significance levels make these results not entirely conclusive). We argue that expected profits of electric generating companies did not fall because the regulated price of electricity was typically allowed to increase with costs. In the electricity industry, the costs of the CAAA were expected to be borne entirely by consumers in the form of higher prices.
Keywords: 330